Análisis comparativo entre el Régimen Pensional de Prima media (rpm) y el Régimen de Ahorro Individual con Solidaridad (RAIS) en Colombia (2019)
Pensioning in Colombia is considered a privilege, factors such as the increase in unemployment and the deterioration of job stability, do not facilitate the process to access a pension allowance. Although reform is necessary, one should not fall into the belief that there is no pension future for the country. In the current pension systems (RPM and RAIS), more than 22 million Colombians are affiliated, which are the result of joint work by the State, pension administrators (Colpensiones, Porvenir, Proteccion Colfondos and Old Mutual) and workers.